2019
DOI: 10.1155/2019/2386163
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing Effects of Clematis apiifolia DC. Extract against Benzo[a]pyrene-Induced Damage to Human Keratinocytes

Abstract: Background. Benzo[a]pyrene (B[a]P), a polycyclic aromatic hydrocarbon present in the atmosphere, has cytotoxic and carcinogenic effects. There have been no reports to demonstrate involvement of Clematis apiifolia DC. extract (CAE) in B[a]P-induced effects. This study was conducted to investigate the effect of CAE on B[a]P-induced effects and to elucidate its mechanism of action in HaCaT human keratinocytes. CAE inhibited aryl hydrocarbon receptor (AhR) signaling by decreasing both XRE reporter activity and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Furthermore, the status of AHR nuclear translocation was assessed, since an Src inhibitor Dasatinib reportedly prevents BaP-induced AHR nuclear translocation and inhibits the effect of BaP [ 62 ]. Dasatinib was used as a positive control, which inhibits BaP-induced AHR nuclear translocation by inhibiting Src.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the status of AHR nuclear translocation was assessed, since an Src inhibitor Dasatinib reportedly prevents BaP-induced AHR nuclear translocation and inhibits the effect of BaP [ 62 ]. Dasatinib was used as a positive control, which inhibits BaP-induced AHR nuclear translocation by inhibiting Src.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of Src was upregulated by BaP in HaCaT cells, which was downregulated in the presence of BAI, as in NHEKs (Figure 7b, Supplementary Figure S8b). Furthermore, the status of AHR nuclear translocation was assessed, since an Src inhibitor Dasatinib reportedly prevents BaP-induced AHR nuclear translocation and inhibits the effect of BaP [62]. Dasatinib was used as a positive control, which inhibits BaP-induced AHR nuclear translocation by inhibiting Src.…”
Section: Bap-induced Src Phosphorylation and Ahr Nuclear Translocatiomentioning
confidence: 99%
“…Cell proliferation or cellular senescence has been considered as one of the main hallmarks of skin aging [ 27 ]. Recent studies have reported the involvement of senescent cells in skin aging and aging-related diseases [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…MuLV reverse transcriptase was used to synthesize cDNA from the total RNA (1 μg) according to the manufacturer’s instructions. RT-PCR results was analyzed as previously reported [ 19 ]. The data were normalized to the expression level of three housekeeping genes such as GAPDH, 18S, and HPRT.…”
Section: Methodsmentioning
confidence: 99%
“…Various reports have demonstrated the cytotoxic, carcinogenic, oxidative stress, and mutagenic effects of B[a]P [ 17 , 18 , 19 , 20 ]. However, until now, there have been only a few reports regarding the development of compounds to reduce the toxicity of B[a]P [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%